2015
DOI: 10.1177/2050312115598250
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of plasma amyloid 1-42 and tau as biomarkers for Alzheimer’s disease

Abstract: Objective:Amyloid 1-42 (Aβ42) and tau in cerebrospinal fluid are currently used as markers for diagnosis of Alzheimer’s disease. Conflicting reports exist regarding their plasma levels in Alzheimer’s disease patients. A meta-analysis was performed to statistically validate the use of plasma Aβ42 and tau as biomarkers for Alzheimer’s disease.Methods:Different databases were searched using the search key: (amyloid OR amyloid1-42 OR Aβ42) AND (tau OR total tau) AND plasma AND (alzheimer’s OR alzheimer’s disease),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…Because authors of previous meta-analyses have not found any significant difference between the total plasma Aβ 40 and Aβ 42 levels in patients with AD and control individuals [ 19 24 ], detecting crude oligomeric Aβ in plasma was a challenge, owing to its low concentrations in the blood, especially in the midst of several interfering factors at high concentrations. Aβ autoantibodies, albumin, fibrinogen, immunoglobulin, apolipoprotein J, ApoE, transthyretin, α-2-macroglobulin, serum amyloid P component, plasminogen, and amylin [ 19 23 ] could interfere with the detection of oligomeric Aβ by MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Because authors of previous meta-analyses have not found any significant difference between the total plasma Aβ 40 and Aβ 42 levels in patients with AD and control individuals [ 19 24 ], detecting crude oligomeric Aβ in plasma was a challenge, owing to its low concentrations in the blood, especially in the midst of several interfering factors at high concentrations. Aβ autoantibodies, albumin, fibrinogen, immunoglobulin, apolipoprotein J, ApoE, transthyretin, α-2-macroglobulin, serum amyloid P component, plasminogen, and amylin [ 19 23 ] could interfere with the detection of oligomeric Aβ by MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, decline of the plasma Aβ42/Aβ40 ratio has been reported in some studies, while others have reported the opposite result, or no difference 10 . A recent meta-analysis showed that the level of plasma Aβ42 did not vary significantly between AD patients and controls and cannot serve as a reliable marker for the diagnosis of AD 12 . There are several potential causes of contradictory measurements of plasma Aβ levels.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the plasma Aβ 42 level did not show a correlation with the questionnaire score and could not distinguish CCDS dogs from normal dogs. In AD studies, results for the use of plasma Aβ 42 as a biomarker have been controversial [35]. The expression was in contrast with that reported in a previous study, which showed that plasma Aβ was signi cantly gradually decreased in early CCDS and severe CCDS, while the highest Aβ 42 plasma level was observed in younger dogs [7,34].…”
Section: Discussionmentioning
confidence: 69%
“…Even though many candidate biomarkers have been identi ed in both blood and cerebrospinal uid (CSF), none of these markers has been used routinely in the clinic. In previous studies, plasma Aβ 42 was evaluated as a biomarker in AD and CCDS, but it is highly variable and seems to be controversial [7,34,35]. Therefore, the identi cation and characterization of novel biomarkers are necessary for the reliable diagnosis of CCDS.…”
mentioning
confidence: 99%